Multiply functionalized dendrimers: protective-group-free synthesis through sequential thiol-epoxy 'click' chemistry and esterification reaction1. Issue 55 (17th June 2015) - Gadwal, Ikhlas; Khan, Anzar
<x xml:space="preserve">Abstract</x> A protective-group-free synthetic route to multiply functionalized dendrimers is presented.